A practical method to transform frequency dependent impedance to time domain. - Nakamura, Naohiro
In order to perform time history earthquake response analyses with consideration to both the dynamic soil?structure interaction and the non-linear behaviour of the structure, it is important to transform the soil impedance in the frequency domain to the impulse response in the time domain. In this paper, a new transform method with high practicality is proposed. First, the formulation of the proposed transform method is described. Next, the validity of the method is examined using an example problem whose impulse response is analytically obtained. Then, the impedance of the rigid foundation on 2-layered soil is transformed to the time domain, and the characteristics of the impulse response are investigated. Finally, time history earthquake response analyses of a structure on the soil using the obtained impulse response are carried out. The validity and the efficiency of the proposed method are confirmed through these investigations.
Keywords: Soil?structure interaction; Soil impedance; Time domain; Impulse response